Strategy of the Head of Madrasah Administration in Improving the Performance of Educational Personnel: Rotation Resistance and Training Limitations - Putri Kurniawati; Chusnul Chotimah (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
This research is motivated by the importance of the head of administration's strategy in improving the performance of educational staff. Even though the role of administrative staff has been widely studied, there are still gaps regarding the strategy of heads of administration in facing real challenges in madrasas, especially in the context of changing administrative needs and digitalization. This research uses a qualitative phenomenological approach through interviews, observation and documentation. Data analysis was carried out through reduction, presentation and drawing conclusions, with validity testing using triangulation and member checking. The research results show that the strategy of the head of administration includes performance planning, division of tasks according to skills, regular coaching and training, as well as periodic evaluations which contribute to increasing the discipline, effectiveness and professionalism of educational staff. Key challenges include the resistance of some staff to job rotation and limited external training. The solutions taken include routine coaching, personal motivation, open communication, and collaboration with external institutions in organizing training. The implication is that this strategy can be adapted by educational administration managers through strengthening organizational communication and external collaboration in order to improve the performance of educational staff in a sustainable manner.